When the Past Is in the Present: The Paradox of Educational Opportunity and Social Inclusion in South Africa and Rwanda. Issue 4 (October 2019) - Russell, S. Garnett; Carter, Prudence L.
The legacies of a racial and ethnocentric past continue to have implications for the present in South Africa and Rwanda, particularly within the realm of education. Although in both societies, the governments have addressed their repressive and violent histories through the implementation of color-blind (or nonracial/ethnic) policies that espouse national unity and reconciliation, these very same policies inadvertently reinforce old divisions. They suppress candid discussion about past and current intergroup tensions, resulting in a paradox of social inclusion. In this article, the authors interrogate how historically ascribed identities, which were used for the purposes of oppression and social divisions in South Africa and Rwanda, are reconstituted in the postapartheid and postgenocide eras. The authors draw on empirical evidence from case studies of contemporary schools in both countries and argue that the nations' two approaches—nonracialization and nonethnicization, respectively—aim to mute explicit discourse and language about racial and ethnic differences though the spread of "color-blind" ideologies. However, everyday behaviors and attitudes of individuals—students and educators—who are inculcated with ideas of past racial/ethnic ideologies remain rigid and continue to affect micro-level and school-level interactions that undermine the legitimacy of either color-mute or color-blind ideologies and contribute to boundary maintenance.